Actively adjustable step-type ultrasonic horns in longitudinal vibration. (14th April 2018) - Lin, Shuyu; Guo, Hao; Xu, Jie
Abstract: Actively adjustable longitudinal step-type ultrasonic horns are proposed and studied. The horn is composed of a traditional ultrasonic horn and piezoelectric material. In practical applications, this kind of step-type ultrasonic horn is mechanically excited by an ultrasonic transducer and the piezoelectric material is connected to an adjustable electric impedance. In this research, the effects of the electric impedance and of the location of the piezoelectric material on the performance of the horn are studied. It is shown that when the electric resistance is increased, the resonance frequency of the horn is increased; the displacement magnification is increased when the piezoelectric material is located in the large end and decreased when the piezoelectric material is located in the small end of the horn. The displacement magnification for the piezoelectric material in the large end is larger than that for the piezoelectric material in the small end of the horn. Some step-type ultrasonic horns are designed and manufactured; the resonance frequency and the displacement magnification are measured by means of POLYTEC Laser Scanning vibrometer. It is shown that the theoretical resonance frequency and the displacement magnification are in good agreement with the measured results. It is concluded that by means of the insertion of the piezoelectric material in the longitudinal horn, the horn performance can be adjusted by changing the electric impedance and the location of the piezoelectric material in the horn. It is expected that this kind of adjustable ultrasonic horns can be used in traditional and potential ultrasonic technologies where the vibrational performance adjustment is needed. Highlights: Step-type longitudinal horns with adjustable performance are proposed and studied. The active adjustment of resonance frequency and magnification factor is performed. The location of the piezoelectric material has obvious effect on the performance of the horn. The horn with PZT at the large end is superior to that with PZT at the small end.